Human Migration : A Guide to Migration Literature in English 1955-1962 - Mangalam, J. J. (Book collections on Project MUSE., 1968)
In this guide to the literature on human migration, J.J. Mangalam indexes over 2,000 titles that appeared in English from 1955 through 1962. An important feature of this work is the annotation of nearly 400 major articles on migration. These annotations provide information on the main focus of the study, the hypotheses tested, and any special measuring devices employed. The conclusions are also given, using the authors' words whenever possible. To facilitate the use of this guide the author has compiled an index that lists not only the subjects treated but also the major variables used in each.